PENERAPAN MODEL PETA KONSEP UNTUK MENINGKATKAN HASIL BELAJAR PAI DI SMP NEGERI 4 LHOKSEUMAWE - TARMIZI TARMIZI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
Concept map is a learning model by simplifying material from long descriptions to short in the form of maps to make it easier for students to understand a material. The concept map model is appropriate to be applied in PAI learning, especially Islamic Cultural History (SKI). Before using the concept map, student learning outcomes on SKI material were low. The low learning outcomes of students in PAI learning, especially in the field of SKI, one of which is due to the learning model used by the teacher is not right, students are asked to read the SKI material in the form of a fairly long description. This condition makes it difficult for students to find the core of the material they are learning, so that learning outcomes are low. Therefore, teachers need to apply appropriate learning models to be able to stimulate students to learn actively, creatively and innovatively, so as to improve their learning outcomes. This study was designed to conduct research on the application of the concept map model in improving student learning outcomes on SKI material. The research subjects were students of class VII SMP Negeri 4 Lhokseumawe with a total of 42 students. The results showed that the application of the concept map model can stimulate the learning process in the classroom, where students can contribute actively, critically, and innovatively, so that PAI learning outcomes can increase. This can be seen from the implementation of the first cycle, there has been an increase in learning outcomes compared to pre-cycle results, because the score in the first cycle obtained 25 people >70 (according to the KKM) with a percentage of 59.52%. Furthermore, the results of observer observations on teacher activities in the first cycle reached 80.76% and observer observations on student activities reached 78.84%. While the implementation of the second cycle experienced a significant increase, namely 42 students completed with a percentage of 93.23%, with observations on teacher activities reaching 95.19% and observations on student activities reaching 96.15%. ABSTRAKPeta konsep merupakan model pembelajaran dengan menyederhakan materi dari uraian panjang menjadi singkat dalam bentuk peta untuk memudahkan peserta didik memahami suatu materi. Model peta konsep tepat diterapkan dalam pembelajaran PAI khusunya Sejarah Kebudayaan Islam (SKI). Sebelum menggunakan peta konsep, hasil belajar siswa pada materi SKI rendah. Rendahnya hasil belajar peserta didik pada pembelajaran PAI, khususnya bidang SKI, salah satunnya disebabkan model pembelajaran yang digunakan guru belum tepat, peserta didik diminta untuk membaca materi SKI dalam bentuk uraian yang cukup panjang. Kondisi ini membuat peserta didik sulit menemukan inti materi yang dipelajarinya, sehingga hasil belajarnya rendah.Oleh karena itu guru perlu menerapkan model pembelajaran yang tepat agar mampu merangsang peserta didik untuk belajar aktif, kreatif dan inovatif, sehingga dapat meningkatkan hasil belajarnya. Penelitian ini didesain untuk melakukan penelitian terhadap penerapan model peta konsep dalam meningkatkan hasil belajar siswa pada materi SKI. Subjek penelitian adalah peserta didik kelas VII SMP Negeri 4 Lhokseumawe dengan jumlah siswa 42 orang. Hasil penelitian menunjukkan bahwa penerapan model peta konsep dapat membangkitkan proses pembelajaran di dalam kelas, di mana peserta didik dapat berkonstribusi secara aktif, kritis, dan inovatif, sehingga hasil belajar PAI dapat meningkat. Hal tersebut terlihat dari pelaksanaan siklus I sudah mulai ada peningkatan hasil belajar dibandingkan hasil pra-siklus, karena perolehan nilai pada siklus I memperoleh 25 orang >70 (sesuai KKM) dengan persentase 59,52%. Selanjutnya hasil observasi pengamat terhadap kegiatan guru pada siklus I mencapai 80,76% dan observasi pengamat pada kegiatan siswa mencapai 78,84%. Sedangkan Pelaksanaan siklus II mengalami peningkatan secara signifikan, yaitu 42 orang siswa tuntas dengan persentase 93,23%, dengan hasil pengamatan terhadap kegiatan guru mencapai 95,19% dan hasil pengamatan terhadap kegiatan siswa mencapai 96,15%.